Development of a Historical Thinking Skills Assessment Instrument Based on the Evalbee Application for Colonialism and Imperialism Material in High School Students - Agustin, Anik Selviana; Wasino, Wasino; Yuwono, Agus (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
Historical thinking skills are a crucial element within the Merdeka Curriculum. These skills can be defined as the scientific procedures or steps involved in learning history. This research aimed to develop an assessment of historical thinking skills for high school students using the Evalbee application. The study employed a Research and Development (R&D) methodology, specifically the ADDIE model. The developed instrument was deemed feasible based on expert validation and empirical trial evidence. The feasibility achievement included an expert validity score of 0.91, falling within the "very good" category. Expert validity was calculated using Aiken's V formula. Item analysis for both large-scale and small-scale trials utilized the Rasch model, and all items were declared valid. The Cronbach's Alpha reliability coefficient of 0.81 indicates a "good" range.